Representation of Women in the 2018 and 2024 Social Studies Curricula and Textbooks - Bulut, Berra (Bulletin of Educational Studies, 2024)
This study examines the representation of male and female figures in the 2018 and 2024 Social Studies Curricula and the social studies textbooks used in the 2023-2024 academic year. Employing document analysis as a qualitative research method, the findings indicate that women's contributions in science, art, politics, and other domains are insufficiently represented, while male figures predominate numerically. This underrepresentation of female figures hinders female students' ability to find role models and results in an incomplete understanding of history. The study highlights the importance of more balanced gender representation in curricula and textbooks and suggests considering adjustments to address this disparity.